Odpowiedzi

2010-02-17T16:15:28+01:00
A) 8-2x=5x-5
-2x-5x=-5-8
-7x=-13/:7
x= 13/7

b) 3x-3=-3x+3x
3x+3x+3x=3
9x=3/:9
x=1/3

c) 2x+13=30-3x
2x+3x=30-13
5x=17/:5
x=3,4

d) 5(x+1)=2x-5
5x+5=2x-5
3x=0/:3
x=0

e) 3(x+2)=7+2
3x+6=7+2
3x=9-6
3x=3/:3
x=1

f) -4(x+1)=-3(x+2)
-4x-4=-3x-6
-x= -2
x=2
Najlepsza Odpowiedź!
2010-02-17T16:17:59+01:00
A) 8-2x=5x-5
-2x-5x=-5-8
-7x=-13
x=13/7
b) 3x-3=-3x+3x
3x+3x-3x=3
3x=3
x=1
c)2x+13=30-3x
2x+3x=30-13
5x=17
x=17/5
d)5(x+1)=2x-5
5x+5=2x-5
5x-2x=-5-5
3x=-10
x=-10/3
e) 3(x+2)=7+2
3x+6=9
3x=9-6
x=1
f) -4(x+1)=-3(x+2)
-4x-4=-3x-6
-4x+3x=-6+4
-x=-2
x=2
2010-02-17T16:28:05+01:00
A) 8-2x=5x-5
-2x-5x=-5-8
-7x=-13
x=13/7

b) 3x-3=-3x+3x
3x+3x-3x=3
3x=3
x=1

c)2x+13=30-3x
2x+3x=30-13
5x=17
x=17/5

d)5(x+1)=2x-5
5x+5=2x-5
5x-2x=-5-5
3x=-10
x=-10/3

e) 3(x+2)=7+2
3x+6=9
3x=9-6
3x=3
x=1

f) -4(x+1)=-3(x+2)
-4x-4=-3x-6
-4x+3x=-6+4
-x=-2
x=2